Patient-Selection of a Clinical Trial Primary Outcome: The ENHANCE-AF Outcomes Survey. - Randall S Stafford; Eli N Rice; Rushil Shah; Mellanie T Hills; Julio C Nunes; Katie DeSutter; Amy Lin; Karma Lhamo; Bryant Lin; Ying Lu; Paul J Wang (PLoS ONE)
Introduction Before the initiation of the ENHANCE-AF clinical trial, which tested a novel digital shared decision-making tool to guide the use of anticoagulants in stroke prevention for patients with atrial fibrillation, this study aimed to identify the most appropriate, patient-selected primary outcome and to examine whether outcome selection varied by demographic and clinical characteristics. Methods Our cross-sectional survey asked 100 participants with atrial fibrillation to rank two alternative scales based on the scales' ability to reflect their experiences with decision-making for anticoagulation. The Decisional Conflict Scale (DCS), a 16-item scale, measures perceptions of uncertainty in choosing options. The 5-item Decision Regret Scale (DRS) focuses on remorse after a healthcare decision. We included adults with non-valvular AFib and CHA2DS2VASc scores of at least 2 for men and 3 for women. Multivariable logistic regression with backward selection identified characteristics independently associated with scale choice. Results The DCS was chosen over the DRS by 77% [95% confidence interval (CI) 68 to 85%] of participants. All subgroups designated a preference for the DCS. Those with higher CHA2DS2VASc scores (≥5, n = 26) selected the DCS 54% of the time compared with 86% of those with lower scores (<5, n = 74; p =  0.002). Multiple logistic regression confirmed a weaker preference for the DCS among those with higher CHA2DS2VASc scores. Conclusions Individuals with atrial fibrillation preferred the DCS over the DRS for measuring their decision-making experiences. As a result of this survey, the DCS was designated as the ENHANCE-AF clinical trial's primary endpoint.